A floating IP implementation based-on load balancing in cloud computing - Andhyka, Awang; Badri, Fawaidul (International Journal of Engineering and Technology, 2020)
With the advance of technology and constant changes in internet development, cloud computing has poured today. The industrial 4.0 requires technology that is reliable and has high stability. With lower funds and convenience in overcast computing as a serving, for ex-ample, cloud servers, users are increasingly placing web resources and information on cloud computing. But, when needed, by many users, errors or downtime cloud server often occurs on the cloud server. Various kinds of obstacles often happen, such as errors, ISP interrupted, overloaded, or others. From these problems, the availability and reliability system on the cloud server will be increasingly important so that this study will discuss the issue of an encumbrance balancing and floating IP (internet protocol) in a cloud server with a minimum cost. This study proposes a dual balanced approach using floating IP addresses to balance workload in cloud computing. This is to ensure the reliability with the stability of a cloud server to optimize the maximum available resources. Cloud analyst, like a visual-based Cloud Sim Modeler, will be used for algorithm analysis. Comparative studies are also brought out by several algorithms such as the robin algorithm and First Serve algorithm, the results will be analyzed and expected to be a right solution that can later be applied to a need that requires resources with a lot of connectivity, such as e-commerce, revenue new students, online exams, or others.Â Â Â